2015
DOI: 10.1002/pssa.201431764
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled silicon nanocrystal arrays for photovoltaics

Abstract: Silicon nanocrystals (Si NCs) are a promising candidate for the top cell of Si tandem solar cells since their bandgap exceeds that of bulk silicon and can be tuned by adjusting nanocrystal size. Due to this effect, size control is required to maintain a uniform bandgap throughout a Si NC film. This can be achieved by annealing superlattices of Si-rich and stoichiometric dielectrics. This paper reviews the progress that has been made using host matrices SiO2, Si3N4, and SiC. Si NCs in SiO2 show excellent NC siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 51 publications
0
13
0
2
Order By: Relevance
“…3(b)). Further sources for tunnelling sites are any Si rich regions within the SiO2, forming Si nanocrystals (blue circles in neck region) embedded within the SiO2 [50], and these may or may not contain P atoms.…”
Section: Electrical Characterisation and Simulationmentioning
confidence: 99%
“…3(b)). Further sources for tunnelling sites are any Si rich regions within the SiO2, forming Si nanocrystals (blue circles in neck region) embedded within the SiO2 [50], and these may or may not contain P atoms.…”
Section: Electrical Characterisation and Simulationmentioning
confidence: 99%
“…Da vor kurzem diverse Übersichtsartikel zu fundamentalen Entwicklungen von SiNKs in Bioanwendungen, Kernspintomographie und Photovoltaikanwendungen verçffentlicht wurden, werden diese Anwendungen in diesem Aufsatz nicht näher betrachtet. [24,[76][77][78][79] Im Folgenden soll vielmehr auf neue Entwicklungen der SiNKs als aktive Materialien in Batterieelektroden, Sensoren und Dioden, wie auch als Katalysatoren eingegangen werden.…”
Section: Anwendungenunclassified
“…4 Silicon nanoparticles have been studied actively in recent years because they are promising for application in various types of semiconductor devices, such as MOS based nonvolatile memories [5][6][7] and third generation solar cells. [8][9][10][11][12] We have shown that MOS structures with silicon nanocrystals are also promising for detectors of ionizing radiation. 13,14 Most frequently, Si nanoparticles are grown by high temperature thermal annealing of nonstoichiometric silicon oxides, but electron or ion beams irradiation has also been applied as a tool for growing and processing Si nanoparticles.…”
Section: Introductionmentioning
confidence: 99%